Limit bending moment for pipes with two circumferential flaws under combined internal pressure and bending. (February 2016) - Ye, Hao; Qian, Jinyuan; Yan, Sunting; Jiang, Chenghang; Wei, Lin; Jin, Zhi-jiang
Abstract: By assuming the neutral axis is perpendicular to the bending plane, this paper presents a general analytical solution to predict the limit bending moment for pipes with two inner surface circumferential flaws under combined internal pressure and bending moment. The circumferential stress caused by internal pressure is taken into account through Mises yield criterion. Based on the general solution, expressions for symmetrical and unsymmetrical bending with two flaws of the same size are proposed. Then the influence of perpendicularity assumption is discussed and it demonstrates that the deviation caused by perpendicularity assumption is negligible. Finite element analyses and experiments are both carried out. The results calculated by proposed expressions are found to be in good agreement with both numerical results and experimental ones. The effect of several parameters on the limit bending moment is also studied. Results reveal that circumferential stress caused by internal pressure has important influence on bending moment, and should be taken into account. Highlights: A general limit load solution for a pipe with two circumferential flaws is proposed. Solutions of two special cases are proposed. The influence of perpendicularity assumption is discussed. Numerical and experimental verification of proposed solutions have been conducted. The effects of flaw sizes and circumferential stress on limit load are analyzed.